Online Scratch Activities during the COVID-19 Pandemic: Computational and Creative Thinking - Didem Karakaya Cırıt; Selçuk Aydemir (International Journal of Evaluation and Research in Education (IJERE), 2023)
This paper investigated the effect of online Scratch activities on college students’ computational and creative thinking. The study adopted a mixed research design including one group pretest-posttest. The sample consisted of 24 child development undergraduates (23 female and 1 male) in the 2019-2020 academic year. The research was carried out in "Teaching Science and Mathematics in Preschool Education” course and lasted 12 weeks. The participants developed Scratch projects based on eight learning outcomes (four math and four science). Data were collected using the Computational Thinking Scale, the Marmara Creative Thinking Dispositions Scale, and reflective journals. The quantitative data were analyzed using a paired sample t-test. The qualitative data were analyzed using content analysis. The results showed that Scratch activities helped students develop computational and creative thinking.